Penentuan Rute Berbasis Algoritma Genetika (Studi Kasus: Angkutan Wisata Surakarta) - Benyamin Morib, Didik Nugroho, Teguh Susyanto (STMIK Sinar Nusantara, 2013)
Land transport like buses and public transportation is becoming a tool in the dibtuhkan transportation to tourist sites. Solo is one of the most visited tourist attractions where travelers who want to spend a lot of time for play, recreation, or for science in the city solo. However, information about transportation is less visible, and even the manual nature of the process information. Therefore we need a method to solve problems in the field of transport, which will be searched in the search for the closest distance transport journey from the initial position to tourism in the town of Surakarta. Genetic algorithms can be implemented for searching transit lines to attractions in the city of Surakarta. This is expected to help in the journey to the attraction in order to be faster if you know the closest point so that it can minimize the distance from one attraction to another attraction. This study yielded information such as street names as Surakarta travel route, transit lines, the travel distance and total travel animation from the initial position to the departure to the tourist sites. Based on the test results shows that Genetic algorithms can produce close to transport routes are the closest results in the case of the determination of the town of Surakarta tourism transport compared with the results from google maps route vehicles. Keywords: transportation, Genetic algorithms, Surakarta City